Atomic layer deposition of dielectric Y2O3 thin films from a homoleptic yttrium formamidinate precursor and water. Issue 5 (12th January 2021) - Boysen, Nils; Zanders, David; Berning, Thomas; Beer, Sebastian M. J.; Rogalla, Detlef; Bock, Claudia; Devi, Anjana
Abstract : In this work, the application of tris( N, N ′-diisopropyl-formamidinato)yttrium(iii ) [Y(DPfAMD)3 ] as a precursor in a water-assisted thermal atomic layer deposition (ALD) process for the fabrication of device quality Y2 O3 thin films is demonstrated. Abstract : We report the application of tris( N, N ′-diisopropyl-formamidinato)yttrium(iii ) [Y(DPfAMD)3 ] as a promising precursor in a water-assisted thermal atomic layer deposition (ALD) process for the fabrication of high quality Y2 O3 thin films in a wide temperature range of 150 °C to 325 °C. This precursor exhibits distinct advantages such as improved chemical and thermal stability over the existing Y2 O3 ALD precursors including the homoleptic and closely related yttrium tris-amidinate [Y(DPAMD)3 ] and tris-guanidinate [Y(DPDMG)3 ], leading to excellent thin film characteristics. Smooth, homogeneous, and polycrystalline (fcc) Y2 O3 thin films were deposited at 300 °C with a growth rate of 1.36 Å per cycle. At this temperature, contamination levels of C and N were under the detectable limits of nuclear reaction analysis (NRA), while X-ray photoelectron spectroscopy (XPS) measurements confirmed the high purity and stoichiometry of the thin films. From the electrical characterization of metal–insulator–semiconductor (MIS) devices, a permittivity of 13.9 at 1 MHz could be obtained, while the electric breakdown field is in the range of 4.2 and 6.1 MV cm −1 . Furthermore, an interface trap density of 1.25 × 10 11 cm −2 and low leakage current density around 10 −7 A cm −2 at 2 MV cm −1 are determined, which satisfies the requirements of gate oxides for complementary metal-oxide-semiconductor (CMOS) based applications.